Monitoring food system change in Dhaka: Evidence from Dhaka Food System Project - Hossain, Mashiat; Pamuk, Haki; Parvez, Md Shahnewaz; Herens, Marion (Wageningen University & Research, 2024)
The project “Support for Modelling, planning, and Improving Dhaka’s Food System” (DFS) project aimed to address Dhaka’s challenges in providing affordable, accessible, safe, and nutritious food to its residents, using a comprehensive, gender-inclusive, and nutrition-sensitive approach. Dhaka is facing significant challenges to ensure affordability and accessibility of safe and nutritious food to its residents. DFS project aimed to find integrated solutions to address both present and future food needs in Dhaka. The project followed a comprehensive approach that considered various aspects of the food system, including short-term challenges related to food security, availability, and consumption, as well as long-term challenges regarding urban food policy and planning. A gender-inclusive and nutrition-sensitive approach was adopted throughout the project.- The report uses a food system monitoring approach to analyse how the DFS project initiatives connect with Dhaka’s food system. DFS project initiatives target specific aspects and aim to bring transformative changes for improved food outcomes in the city while also being gender-sensitive, food safety and nutrition-focused. This report analyses the connection between the DFS project initiatives and Dhaka’s food system using a food system monitoring approach. Most of the 21 DFS project initiatives are linked to specific aspects of Dhaka’s food system, and three initiatives are expected to contribute to multiple aspects, aiming to bring about changes in the city’s food system. The outputs generated by these initiatives are anticipated to transform the food system and improve food-related outcomes in Dhaka’s four cities. The project initiatives were designed to be gender-sensitive and nutrition-focused, aligning with the project’s overall approach.